Historical-dialectical materialism: contributions to qualitative research in education - Martins, Ligia Marcia [UNESP]; Lavoura, Tiago Nicola (Editora Univ Federal Parana, Centro Politecnico, 2018)
The present text intends to present contributions of the method named historical-dialectic materialism to the qualitative investigations in education. We expect to launch arguments that can serve as foundations and parameters of analysis for research in education, as guided by the scientific premise of the search for the intelligibility of social reality. We will highlight the following theoretical and methodological issues: the relationship between the ontological dimension and the epistemological dimension of reality, as well as the theoretical foundations that support the categories of analysis of the investigated object. Then, we will transpose these precepts into the so-called empirical and theoretical-conceptual researches.
Keywords: Historical-dialectical materialism; Method; Scientific knowledge